2023
DOI: 10.1038/s41598-022-26314-8
|View full text |Cite
|
Sign up to set email alerts
|

BfmRS encodes a regulatory system involved in light signal transduction modulating motility and desiccation tolerance in the human pathogen Acinetobacter baumannii

Abstract: We have previously shown that Acinetobacter baumannii as well as other relevant clinical bacterial pathogens such as Staphylococcus aureus and Pseudomonas aeruginosa, perceive and respond to light at 37 °C, the normal temperature in mammal hosts. In this work, we present evidence indicating that the two-component system BfmRS transduces a light signal in A. baumannii at this temperature, showing selective involvement of the BfmR and BfmS components depending on the specific cellular process. In fact, both BfmR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…BfmR has been shown to be crucial for pellicle and biofilm formation in Acinetobacter baumannii and P. aeruginosa 24 , 27 . Additionally, it plays a pivotal role in the bacterium’s survival at the mammalian host temperature in multiple animal models, contributing significantly to chronic infections 25 , 26 , 29 . It has been reported that BfmR has a potential extensive downstream regulatory network, and BfmS influences the tolerance to certain antibiotics, outer membrane vesicle (OMV) production, and cytotoxicity toward host cells 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BfmR has been shown to be crucial for pellicle and biofilm formation in Acinetobacter baumannii and P. aeruginosa 24 , 27 . Additionally, it plays a pivotal role in the bacterium’s survival at the mammalian host temperature in multiple animal models, contributing significantly to chronic infections 25 , 26 , 29 . It has been reported that BfmR has a potential extensive downstream regulatory network, and BfmS influences the tolerance to certain antibiotics, outer membrane vesicle (OMV) production, and cytotoxicity toward host cells 43 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BfmR has a potential extensive downstream regulatory network, and BfmS influences the tolerance to certain antibiotics, outer membrane vesicle (OMV) production, and cytotoxicity toward host cells 43 . Studies have also begun to shed light on the signals sensed by BfmS, such as light or pressure 29 . Despite these advances, a comprehensive understanding of its complete functional repertoire and its intricate regulatory mechanisms in complex biological processes remains an area necessitating further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…V15 forms robust biofilms, produces a capsule, and generates large amounts of extracellular compounds ( 5 ). Moreover, it responds to light at both environmental temperatures and those of warm-blooded hosts ( 6 ). Furthermore, V15 is sensitive to multiple antibiotics and genetically manipulable.…”
Section: Announcementmentioning
confidence: 99%
“…baumannii commonly employs two-component systems (TCSs) to regulate adaptive responses and virulence-related traits. Most TCSs in bacteria can regulate gene expression related to antibiotic resistance, virulence, biofilm formation [8], and motility [9], and 16 sensor kinases and 17 response regulators have been annotated in A. baumannii to date, with studies previously conducted on one hybrid sensor kinase, A1S_2811 [10], and nine TCS, AdeSR [11], BaeSR [12], BfmSR [13], CntAB [14], EmaSR [15], GacSA [16], OmpR-EnvZ [17,18], PmrAB [19], and StkSR [20] (AmsSR [21]). Of these TCSs, many were found to regulate gene expression related to antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%